Amino acids as selective acylating agents: regioselective N-1-acylation of imidazolidin-4-one derivatives of the antimalarial drug primaquine - Nuno Vale (2008)
The acylation of bioactive primaquine-based imidazolidin-4-ones was studied using N-chi-Boc-protected glycine as acylating agent. Two synthesis routes, eight different coupling methods and seven distinct solvents were compared. Mild carbodiimide-based couplings on high dielectric constant solvents such as DMF or MeCN increased acylation yields, whereas alcohols inhibited carbodiimide-mediated acylations to take place. Achievement of the synthetic goals was limited by the size of the imidazolidin-4-one ring substituents R-1, R-2 and R-3, but resort to MW-assisted synthesis allowed overcoming such obstacle, though with very modest reaction yields. All reactions involving a Boc-protected amino acid were regioselective, independent of reaction conditions employed. In contrast, regioselective acetylation of the imidazolidin-4-ones could only be achieved by resort to very mild coupling procedures.